11th World Congress of Performance Analysis of Sport 2017
DOI: 10.14198/jhse.2017.12.proc3.01
|View full text |Cite
|
Sign up to set email alerts
|

2015 Badminton World Championship: Singles final men’s vs women’s behaviours

Abstract: The purpose of the current study was to identify players' behaviours and to assess differences between genders at final singles matches of 2015 Badminton World Championship, focusing on time events, shots and court movements. Final men's (MS) and women's (WS) singles matches of 2015 Yakarta World Championship were analysed (150 points and 967 actions). Official videos from Badminton World Federation were used to carry out the post-event analysis. Variables analyzed were: 'timing factors', type of 'shots' and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 2 publications
7
26
0
4
Order By: Relevance
“…For the serve, we found that a short serve was more frequent than a deep serve in both modalities. Valldecabres et al (2015) showed similar results indicating a short serve as more common, while reflecting that a deep serve was an infrequent stroke. The type of a serve used may be influenced mainly by the number of players and Journal of Human Kinetics -volume 71/2020 http://www.johk.pl not so much by the area used.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…For the serve, we found that a short serve was more frequent than a deep serve in both modalities. Valldecabres et al (2015) showed similar results indicating a short serve as more common, while reflecting that a deep serve was an infrequent stroke. The type of a serve used may be influenced mainly by the number of players and Journal of Human Kinetics -volume 71/2020 http://www.johk.pl not so much by the area used.…”
Section: Discussionmentioning
confidence: 61%
“…Badminton appeared in Asia and Europe more than 2000 years ago (Tan et al, 2016). Badminton is a racket sport played by two or four players on a rectangular court (Lees, 2003;Tan et al, 2016), characterized by intermittent efforts of high intensity and short duration (Abián-Vicén et al, 2012;Cabello and Gonzalez-Badillo, 2003;Valldecabres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Badminton smash is one of the most important techniques in badminton games because a smash is one sharp stroke down through the net which aims to get as many points as possible to achieve victory (strike hit). According Valldecabres et, al., [2] badminton is a game consisting in hitting the shuttlecock across the other side of the court over the net, trying to send it to the area in the opponent's side where it is hardest for them to hit it back. Therefore, the main goal of the smash is to overpower the opponent.…”
Section: A Badminton Smash Skillsmentioning
confidence: 99%